Voluntary Counseling and Testing for HIV in Rural Area of Democratic Republic of the Congo: Knowledge, Attitude, and Practice Survey among Service Users - Mida Kautako-Kiambi; Mathilde B. Ekila; Smith Kama-Lemba; Roger Wumba; Michel N. Aloni (Journal of Tropical Medicine)
Aims. To determine the prevalence of HIV, the level of sexual risk for HIV, and determinants of VCT attendance among adult population living in a rural area. Methods. A cross-sectional study was conducted in Mbanza-Ngungu, Democratic Republic of the Congo. An anonymous questionnaire was designed to extract relevant data. Results. In our cohort, 69% were respondents of more than 24 years of age and the single marital status was most represented (64.1%). A high proportion of respondents (90.6%) visited VCT service for requiring information (good acceptability). Positive test for HIV was reported in 9.4% of respondents. In this cohort, 49.6% of respondents had declared themselves to never use condom. In binary analysis, there was association between positive HIV test and age (p=0.04) and religions (p=0.02). In this cohort, it was observed that positive HIV test was significantly associated with confidentiality (p=0.02). However, there was no association between positive HIV test and condom use (p=0.25), knowledge of VCT (p=0.81), service requested (p=0.20), and previous HIV test (p=0.68). Conclusions. Preventive information for AIDS should be recommended in the population living in rural zone.